# math functions question

Discussion in 'Community Discussion' started by waloshin, Apr 6, 2009.

1. ### waloshin macrumors 68040

Joined:
Oct 9, 2008
#1
On question number 3 , is that a typo because I dont understand the question. If not could you give me an example on how to do it?

File size:
27 KB
Views:
63

Joined:
Mar 7, 2007
Location:
Texas
3. ### waloshin thread starter macrumors 68040

Joined:
Oct 9, 2008
#3
I understand the basics:

If f(x) is = 6x+1
and g(x) is = x+9

Then find f(x) + g(x)

6x + 1 + x + 9

= 7x + 10

4. ### Shaun.P macrumors 68000

Joined:
Jul 14, 2003
Location:
Omicron Persei 8
#4
For f(x) = g(x) let the two functions equal each other. That means 2*x^2 - x [f(x)] = 3*x + 6 [g(x)].

You need to move everyone to one side, such that it will equal 0. Simplify and factorise.
E.g:

2*x^2 - x = 3*x + 6

Move everything to the LHS:

=> 2*x^2 - 4*x - 6 = 0

Divide by common factor of 2:

=> x^2 -2*x - 3 =0

This factorises to:

=> (x-3)(x+1)=0

[Hopefully you will know how to factorise this].

=> x=3 or x=-1.

5. ### jodelli macrumors 65816

Joined:
Jan 6, 2008
Location:
#5
x=3

edit: ShaunPriest got it.

6. ### darklyt macrumors regular

Joined:
Jun 5, 2007
#6
Based on ShaunPriest's answer, you're just solving for the points of intersection. If you graph the functions together, the solutions are where the graphs of the functions cross one another. (Just so you have another interpretation.)

7. ### Shaun.P macrumors 68000

Joined:
Jul 14, 2003
Location:
Omicron Persei 8